Peran Pemerintah Dalam Menyelamatkan Naskah Kuno Minangkabau Pasca Gempa Pada Untuk Pelestarian Budaya Masyarakat Minangkabau - Viola Dewi Putri Syarif (Pustakaloka, 2015)
The manuscripts of Minangkabau has many content about society, lives, and rules, such as the story of the batle that happened at that time, infuential scholars, the natural disasters that have occurred,and traditional medicine,  all  of  it  be writen with  beautiful  handwriting letered Arabic and Malay. On September 30, 2009 an earthquake with a strength of 7.9 on the Richter scale destroyed half of West Sumatera regions, include the buildings of information centers,and the storage areas of ancient texts Minangkabau. That makes all of ancients texts lost and broken. These manuscripts are original publications and unparalleled. This research is to know how the government’s role in saving the post-earthquake  ancient  manuscripts,  for  cultural  preservation  society  of Minangkabau. This study is qualitative, using interview, observationand documentation.  This  study  shows  that  in  the  preservation  of  the collection of ancient manuscripts damaged after  the  earthquake, West Sumatera provincial government assisted by the National Library team in  repairing  damaged manuscripts  collection. National  library  team brings 17 boxes of ancient manuscripts Minangkabau to be treated. And to replace the lost collection, the government is conducting  a search of the ancient manuscripts in houses to the public because there are still many collection of ancient manuscripts held by the public.